Modulation of T cell proliferation and cytokine response by Plumbagin, extracted from Plumbago zeylanica in collagen induced arthritis - Poosarla Aparanji; DN Rao; Athota Rama; Sunkara Venu (BMC, 2011)
Abstract Background The extracts of Plumbago zeylanica have been used in China and other Asian countries as folk medicine for the treatment of cancer, rheumatoid arthritis and dysmenorrhoea. Effect of Plumbagin (5-hydroxy-2-methyl-1,4-naphthoquinone) purified from Plumbago zeylanica on Con A induced T cell proliferation was studied in spleen cells from collagen induced arthritic DBA/1 mice. Methods The DBA/1 mice (five per each group) were immunized with 0.1 mL of collagen (emulsified in CFA) by intradermal injection at the base of the tail. On day 20, mice were given a booster dose of collagen (emulsified in IFA) through the same route. Plumbagin was given at different concentrations (3.3, 6.6, 13.3 mg/kg body weight) intraperitoneally. Control mice received olive oil alone. The Con A induced T cell proliferative responses of arthritic and Plumbagin treated mice were studied by cell culture experiments using tritiated Thymidine. In addition the cytokine levels were estimated from the in vitro spleen culture supernatants of arthritic mice primed with different concentrations of Plumbagin by ELISA. Results Plumbagin enhanced the decreased Con A induced T cell proliferation and Interleukin-2 production in arthritic mice. Moreover elevated levels of IFN- γ were found to be decreased in Plumbagin treated spleen cell culture supernatants. Subclasses of IgG were found to be decreased by Plumbagin treatment, IgG2a reduction seems to be more prominent. Conclusion The results obtained in the current study indicate that Plumbagin is very effective in the mechanism based treatment of Rheumatoid arthritis.